2024
DOI: 10.3389/fpls.2024.1336884
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the potential of cellulose nanofibre based nitrogen fertilizer and its transformative effect on Vigna radiata (Mung Bean): nanofibre for sustainable agriculture

Neha Sharma,
Mandira Kochar,
Benjamin James Allardyce
et al.

Abstract: IntroductionFertilizer management is crucial to maintaining a balance between environmental health, plant health, and total crop yield. Farmers are overutilizing fertilizers with a mind set to enhance the productive capacity of the field, which adversely impacts soil fertility and causes serious environmental hazards. To mitigate the issues of over-utilization of fertilizers, controlled-release fertilizers were developed using nitrogen fertilizer (ammonium chloride) loaded on cellulose nanofibres (named CNF*N)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Jayarambabu et al also reported the ZnO NPs for the study of the growth pattern of Vigna radiata . Sharma et al used cellulose nanofiber-based nitrogen fertilizers as a growth enhancer of Vigna radiata . However, there are a few reports available for the study of the growth pattern of Vigna radiata using hydrogels and other materials.…”
Section: Introductionmentioning
confidence: 99%
“…Jayarambabu et al also reported the ZnO NPs for the study of the growth pattern of Vigna radiata . Sharma et al used cellulose nanofiber-based nitrogen fertilizers as a growth enhancer of Vigna radiata . However, there are a few reports available for the study of the growth pattern of Vigna radiata using hydrogels and other materials.…”
Section: Introductionmentioning
confidence: 99%